Ask more : the power of questions to open doors, uncover solutions, and spark change - Sesno, Frank (AMACOM American Management Association, 2017)
Questions help us break down barriers, discover secrets, solve puzzles, and imagine new ways of doing things. But few of us know how to question in a methodical way. Emmy-award-winning journalist and media expert Frank Sesno aims to change that with Ask More. From questions that cement relationships, to those that help us plan for the future, each chapter in Ask More explores a different type of inquiry. By the end of the book, you'll know what to ask and when, what you should listen for, and what you can expect as the outcome. Both intriguing and inspiring, Ask More shows how questions convey.